Chronic intrathecal baclofen administration in severe spasticity (1990)
On the basis of previous experimental and clinical studies, 14 patients with severe spasticity due to central or spinal cord damage, resistant to all conservative treatments, were selected after a percutaneous trial period for chronic intrathecal baclofen infusion by programmable pumps. The agent was delivered at C4 in quadriplegic patients or in cases with central spasticity and in the neighbouring areas on the affected segments in paraplegic patients. The daily baclofen dose varied from 25 to 260 µg and was infused in a bolus, continuously infused or both combined according to the results during the trial period. After a mean follow-up period of 11 months, constant decrease of rigidity, absence of spasms, improvement of bladder function, cramping pain remission, and moderate improvement in walking capacity and transfer activities were usually observed. Neither complications nor side effects were noted.